A highly sensitive UPLC-MS/MS method for the quantification of the organic cation transporters' mediated metformin uptake and its inhibition in cells - Bajraktari-Sylejmani, Gzona; Bay, Cindy; Gebauer, Lukas; Burhenne, Jürgen; Weiß, Johanna; Sauter, Max (Molecules, 2024)
Metformin is the gold standard substrate for evaluating potential inhibitors of the organic cation transporters (OCTs). Here, we established a UPLC-MS/MS assay to quantify metformin in cell pellets with a range of 0.05-50 ng/mL using 6-deuterated metformin as an internal standard. We used an ion-pairing chromatographic approach with heptafluorobutyric acid, making use of a reverse-phase column, and overcame the associated ion-suppression via previously established post-column injection of aqueous ammonia. The assay was validated according to the Food and Drug Administration (FDA) and the European Medicines Agency (EMA) recommendations for bioanalytical methods. The established extraction procedure was simple, very fast and ensured almost 100% recovery of the analyte. The exceptionally sharp peak form and retention of the ion-pairing chromatography are superior to other methods and allow us to measure as sensitively as 0.05 ng/mL. We used the herein established and validated method to develop a cellular OCT inhibition assay by using metformin as a substrate and human embryonic kidney cells (HEK) overexpressing the OCTs 1-3. The method presented may be useful for identifying new OCT inhibitors, but also for drug-drug interactions and other pharmacokinetic studies, where accurate quantification of low metformin amounts in relevant tissues is mandatory.